The use of (99m}Tc-Al[2]O[3] for detection of sentinel lymph nodes in breast cancer; AIP Conference Proceedings; Vol. 1760 : Physics of Cancer: Interdisciplinary Problems and Clinical Applications 2016 - Sinilkin I. G. Ivan Gennadjevich; Chernov V. I. Vladimir Ivanovich; Medvedeva А. А. Anna Aleksndrovna; Zelchan R. V. Roman Vladimirovich; Slonimskaya E.; Doroshenko A.; Varlamova N. V. Natalya Valeryevna; Skuridin V. S. Viktor Sergeyevich (2016, 2016)
Title screen